High-fidelity database of supercritical homogeneous isotropic turbulence in the pseudo-boiling region - David Martín; Lluís Jofre (Scientific Data)
Abstract Supercritical fluids operate above their critical point and are characterized by strong nonlinearities in the equation of state, highly non-ideal fluid behavior, and a tight coupling between thermodynamics and transport properties. As a result, supercritical fluid flows behave fundamentally different from their low-pressure counterparts. The thermodynamic space of supercritical fluids is commonly divided into two main regions separated by the pseudo-boiling region, where a second-order phase transition occurs. Transcritical flows—those crossing the pseudo-boiling line—undergo substantial variations in thermophysical properties. Additionally, near the pseudo-boiling line, smaller-than-Kolmogorov thermal scales are generated, which are tightly coupled with small velocity scales. The complex two-way interaction between pseudo-boiling phenomena and turbulence remains an open question, both from a fundamental physics perspective and for modeling efforts. In this regard, a database of homogeneous isotropic turbulence under various supercritical thermodynamic conditions in the vicinity of the pseudo-boiling line is presented. The dataset includes instantaneous three-dimensional turbulent flow fields and real-fluid thermophysical quantities, as well as Reynolds- and Favre-averaged data, enabling the study and modeling of transcritical fluid turbulence.